Somatostatin analogues in the therapy of neuroendocrine tumors: Indications, contraindications, side-effects - Beata Polowczyk (Postępy Higieny i Medycyny Doświadczalnej, 2020)
The presence of somatostatin receptors (SSTRs) is crucial in planning the therapy of patients with neuroendocrine tumors. This applies especially to patients in whom surgery has proven unsuccessful or there are contraindications for it. Increased SSTR expression has been observed in many cancers originating in the neuroendocrine system. Among them we distinguish anterior pituitary adenomas producing GH in excess and leading to the development of acromegaly, adenocorticotropic adenomas that autonomously synthesize ACTH, which leads to the development of ACTH-dependent Cushing’s syndrome (Cushing’s disease), as well as adenomas of the anterior pituitary from thyrotropic cells. Rich expression of these receptors has been confirmed in epithelial tumors of neuroendocrine origin in the gastrointestinal tract, pancreas and lungs. Somatostatin analogues, also called somatostatin receptor ligands, are effective in symptomatic therapy; they enable disease control, exhibit anti-proliferative effects and allow hormonal balance, which reduces mortality among patients and improves their quality of life. The antitumor effect of somatostatin analogues has been proven in in vitro and in vivo studies. In therapy they are usually well tolerated and safe. For many years, somatostatin analogues have maintained an important place in the treatment of neuroendocrine tumors and are still the subject of many studies. The aim of the study is to analyze, based on available literature, therapeutic indications for the use of somatostatin analogues, taking into account contraindications for therapy and its possible side effects.